2013
DOI: 10.1186/2251-6581-12-16
|View full text |Cite
|
Sign up to set email alerts
|

Pilot educational program to enhance empowering patient education of school-age children with diabetes

Abstract: BackgroundNurses have a crucial role in patient education of children with type 1 diabetes, but they often exhibit lack of knowledge of the patient education process. This study aimed to describe an educational program to enhance empowering patient education process for the blood glucose monitoring education of school-age children and nurses’ perceptions of using empowering techniques.MethodsAn empowering patient education process for the diabetes education of school-age children was developed. The researcher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 23 publications
(47 reference statements)
0
18
0
Order By: Relevance
“…In order to implement an educational activity that leads to positive outcomes, it is maintained that health care professionals must be trained. This argument is supported by Kelo et al [56], who also examined how nurses perceive the utilisation of empowering education in school-aged children with diabetes and their parents. The study identified four phases or categories for successfully managing this process: assessment of knowledge, skills and needs, planning, implementation, including participation and interactivity, and finally evaluation and feedback for the family.…”
Section: Professionals In the Organisationmentioning
confidence: 56%
See 3 more Smart Citations
“…In order to implement an educational activity that leads to positive outcomes, it is maintained that health care professionals must be trained. This argument is supported by Kelo et al [56], who also examined how nurses perceive the utilisation of empowering education in school-aged children with diabetes and their parents. The study identified four phases or categories for successfully managing this process: assessment of knowledge, skills and needs, planning, implementation, including participation and interactivity, and finally evaluation and feedback for the family.…”
Section: Professionals In the Organisationmentioning
confidence: 56%
“…The study identified four phases or categories for successfully managing this process: assessment of knowledge, skills and needs, planning, implementation, including participation and interactivity, and finally evaluation and feedback for the family. It was stressed that educating children must be based on developmental psychology because of the various psychological and functional abilities that characterise the different ages [56,65]. The study describes the complexity of an empowering patient education in detail, as well as the variety of approaches used.…”
Section: Professionals In the Organisationmentioning
confidence: 99%
See 2 more Smart Citations
“…While Kelmo developed an example of an evidence-based patient education program. Other factors supporting changes in work practices require consideration for further development of the model [15]. Therefore, we evaluated the Partnership Care plan for increasing the interaction between patient, nurse, and physician to monitor and control the conditions of diabetic patients.…”
Section: Introductionmentioning
confidence: 99%